(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Boulgueraguer Z, Chaffai H, Gasmi L, Djabri L, Hani A. 2022. Impact of organic and microbiological pollution on the quality of water in Boussellam Valley and its environment, Setif City, Northeast Algeria. Biodiversitas 23: 2621-2629. Water pollution is a major threat and a global challenge that endangers life on earth at risk because water plays a major role in daily life. Several sources of water pollutants, i.e., organic, industrial, domestic and microbial pollution, may trigger an outbreak of water-borne diseases. Boussellam Valley crosses the Quaternary formations, which dominate the extent of the plain surrounding the region of Sétif in the North-East of Algeria. It is one of the main water resources, mainly for drinking water supply and irrigation. The shallow water table composed of the geological formations containing this aquifer is very heterogeneous in texture and varies considerably from upstream to downstream of the sub-watershed. Thus, the North and East zones are marked by chloride-calcium facies, the central part by a Bicarbonate-calcium facies. At the same time, sulfate-magnesium facies characterize the West zone. This study aimed to evaluate the pollution by organic elements: nitrites, nitrates, and microbiological elements: total and fecal coliforms and streptococci and their impact on the water quality. Samples were collected during May and June 2021 from 5 stations along the valley, and 18 wells were spread out on the plain. The analysis of nitrites and nitrates was carried out by liquid chromatography. In addition, the colony counting of coliforms and streptococci was carried out according to the recommendations of the Algerian water company. The results show an increase in the concentration of nitrites, nitrates, total and fecal coliforms, and the streptococci, particularly in valley waters with very high levels that exceed the normal threshold of drinking water. This increase may be due to wastewater discharges and the intensive use of fertilizers, septic tanks, leaching of animal manure, runoff water, and rearing of domestic or wild animals. The increased levels of nitrites, nitrates, total and fecal coliforms, and the streptococci increase the risk of the vulnerability of the waters of the plain to pollution and degradation of surface waters and the environment in general.